Incorporating Green Growth and Sustainable Development Policies into Structural Reform Agendas - Organisation for Economic Co-operation and Development (World Bank, Washington, DC, 2017)
This report examines how green growth and sustainable development policies can be incorporated into structural reform agendas. Indeed, as demonstrated in the report, many of these policies are closely linked and synergistic with the framework policies applied by G20 governments in their efforts to pursue strong and sustainable growth. The report, has been prepared in response to the request from G20 Finance Ministers and Central Bank Governors in their communication of 25-26 February 2012 that asked the Organization for Economic Co-operation and Development (OECD), with the World Bank and the United Nation (UN), to prepare a report that provides options for G20 countries on inserting green growth and sustainable development policies into structural reform agendas, tailored to specific country conditions and level of development. The report will be an input to the G-20 leader's summit in Los Cabos and provides a toolkit of policy options from which countries may draw-upon when designing their own green growth strategies. The G20 development working group has also tasked the International Organizations with the development of a non-prescriptive toolkit of policy options to support inclusive green growth in the context of sustainable development and poverty eradication in developing countries.